Interactions in low-dimensional spinor bosonic gases - Kolezhuk, A.K. (Физика низких температур, 2010)
Renormalization group approach for low-dimensional dilute Bose gases is generalized for the case of multicomponent bosons. As an example, systems of two- and three-component spinor bosons are considered. It is shown that interatomic interactions are strongly renormalized with a tendency to enhance the interaction symmetry.